Analisis Usaha Agroindustri Ladu di Desa Malangbong - Sulis Solawati Nurul Fauziah; Tito Hardiyanto Tito Hardiyanto; cecep pardani (Jurnal Dimamu, 2026)
Sticky rice ladu is one of the traditional food products made from sticky rice flour and has economic potential to be developed as a superior commodity from Malangbong Village, Malangbong District, Garut Regency. The purpose of this study is to provide an understanding of expenditure, income, profit, and ratio of income to R/C costs of sticky rice ladu agroindustry in Malangbong Village, Malangbong District, Garut Regency at one stage of production activities. This research is a quantitative descriptive study using a case study approach on four glutinous rice ladu artisans selected through a census. Data analysis was conducted based on one production cycle to determine total expenses, income, profits, and the R/C ratio. Based on the research results, it can be seen that the average total production cost of sticky rice dumplings per process is Rp760,328.88. The average income earned reaches Rp1,110,000, resulting in an average profit of Rp349,671.12, the average R/C ratio at 1.48 in one stage of the production process. This means that every Rp1.00 spent by the artisan generates Rp1.48 in revenue, resulting in a profit of Rp0.48. Therefore, the sticky rice ladu agro-industry in this region is considered highly profitable and feasible.